Archaeological anthropology : an introduction to prehistory - Indrani Chattopadhyaya (B.R, 2019)
In certain respect Archaeology enjoys a unique position in social sciences. In European tradition it developed as a historical science, but since the growth of New Archaeology, it has acquired proximity with anthropology, on the one hand, and natural sciences, on the other. According to a radical view it is understood as a hermeneutically informed dialectical science of past and present. This book deals with some basic concepts of archaeological anthropology. Some of the ideas described here were aired to a generation of Delhi University undergraduates and postgraduates since 1997. The text owes much to the relentless demands of and inspiration from my students who made me aware of their needs during all these years. It has been written to view archaeology, that is the material embodiment of the culture, with a wide range of approaches to the past. It seems to me that far from becoming submerged within other disciplines, archaeology has become better able to define itself as a distinct and productive area of study. Archaeology s maturity as a discipline allows it to claim an independent personality with distinctive qualities to contribute